REGULATORY CHALLENGES IN AFRICA An Empirical Analysis - Mark J. Mwandosya (Dar es Salaam Mkuki na Nyota Publishers Ltd, 2021)
Regulation as a tool for pursuing equitable national development and the provision of adequate goods and services is an often enigmatic and inadequately understood subject.
Include indexs and photography
Keywords: Tanzania